A Novel Chimeric Gene, siren, With Retroposed Promoter Sequence in the Drosophila bipectinata Complex - Nozawa, Masafumi (Copyright © 2005 by the Genetics Society of America, 2005)
Retrotransposons often produce a copy of host genes by their reverse transcriptase activity operating on host gene transcripts. Since transcripts normally do not contain promoter, a retroposed gene copy usually becomes a retropseudogene. However, in Drosophila bipectinata and a closely related species we found a new chimeric gene, whose promoter was likely produced by retroposition. This chimeric gene, named siren, consists of a tandem duplicate of Adh and a retroposed fragment of CG11779 containing the promoter and a partial intron in addition to the first exon. We found that this unusual structure of a retroposed fragment was obtained by retroposition of nanos, which overlaps with CG11779 on the complementary strand. The potential of retroposition to produce a copy of promoter and intron sequences in the context of gene overlapping was demonstrated.